2005
DOI: 10.1073/pnas.0500929102
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of vault nanocapsules with enzymatic and fluorescent properties

Abstract: One of the central issues facing the emerging field of nanotechnology is cellular compatibility. Nanoparticles have been proposed for diagnostic and therapeutic applications, including drug delivery, gene therapy, biological sensors, and controlled catalysis. Viruses, liposomes, peptides, and synthetic and natural polymers have been engineered for these applications, yet significant limitations continue to prevent their use. Avoidance of the body's natural immune system, lack of targeting specificity, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
214
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(221 citation statements)
references
References 18 publications
7
214
0
Order By: Relevance
“…Thus far, the highest resolution reconstruction of vaults (16 Å) is from the CP-MVP construct used to form vaults in this study (10). The reconstruction of the CP-MVP recombinant vault appeared virtually identical on the exterior to reconstructions of vaults isolated from rat tissue (10,23), and spectroscopic results from this and previous studies using luciferase assays and fluorescence quenching indicate that the vault interior is only accessible over time (24). Therefore, some mechanism must allow for a significant modification of the vault structure that is not readily apparent in the static 3-D image that enables entry of large proteins into its interior.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Thus far, the highest resolution reconstruction of vaults (16 Å) is from the CP-MVP construct used to form vaults in this study (10). The reconstruction of the CP-MVP recombinant vault appeared virtually identical on the exterior to reconstructions of vaults isolated from rat tissue (10,23), and spectroscopic results from this and previous studies using luciferase assays and fluorescence quenching indicate that the vault interior is only accessible over time (24). Therefore, some mechanism must allow for a significant modification of the vault structure that is not readily apparent in the static 3-D image that enables entry of large proteins into its interior.…”
Section: Discussionmentioning
confidence: 82%
“…Using cryoEM it has been previously shown that co-infection of a single insect cell culture with baculoviruses expressing MVP and either VPARP, TEP1, or both proteins leads to the formation of vaults containing the expected protein components in the vault interior (10). The recombinant MVP-only vaults have also been shown to sequester co-expressed luciferase-INT or GL-INT described above (24). Furthermore, the activity of these two proteins could be shielded from the external environment by the thin protein shell of vaults.…”
Section: Vparp and Tep1 Associate With Pre-formed Mvp Recombinant Vaultsmentioning
confidence: 99%
See 3 more Smart Citations